Mapping of energy potential through annual crop residues in Turkey - Karaca, Cengiz (International Journal of Agricultural and Biological Engineering, 2015)
The objective of this study was to determine the annual crop residue potential in terms of types, quantities and mapping in Turkey. The calorific values of agricultural residues were determined by calorimeter according to ASTM D 5865 Standard Test Method for Coal and Coke 2002. In this study, the energy potential of annual crop residues was evaluated by ArcGIS which is a geographical information system program. The total amount of unused annual crop residues was approximately 15.24 Mt/a. It was found that the total calorific value of the field crop residues was around 268 PJ/a for the 2012 production period in Turkey. The major crops included in the ratio of the total calorific value were maize (45.81%), wheat (21.30%), sunflower (15.10%) and cotton (18.1%). The amount of CO2 emitted into the atmosphere can be reduced by 30 Mt/a year through the use of agricultural residues.Keywords: agricultural residue, exploitable energy potential, mapping, GIS, TurkeyDOI: 10.3965/j.ijabe.20150802.1587